2022
DOI: 10.1155/2022/9282733
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Gene Action, Combining Ability, and Heterosis to Identify Superior Aromatic Rice Hybrids Using Artificial Neural Network

Abstract: The aromatic rice represents a smaller but independent rice collection, the quality of which is considered to be highly acceptable. Farmers are interested in growing aromatic rice due to high premium market price. The prime objective of this study was to enhance genetic improvement of aromatic rice. Combining ability analysis (GCA and SCA) and gene action are studied in a set of 7 × 7 half-diallel crosses. Twenty-one hybrids along with their seven parents were assessed in randomized complete block design. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The use of heterosis breeding offers the possibility of improving the quantitative traits in cross-pollinated crops. Sunny et al [ 21 ] reported that per se evaluation is often ineffective for parental selection on yield-related traits due to their polygenic nature. The selection can be more biased due to unstable performance across environments and weaker vigor due to inbreeding depression [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of heterosis breeding offers the possibility of improving the quantitative traits in cross-pollinated crops. Sunny et al [ 21 ] reported that per se evaluation is often ineffective for parental selection on yield-related traits due to their polygenic nature. The selection can be more biased due to unstable performance across environments and weaker vigor due to inbreeding depression [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heterosis, also known as hybrid vigor, is the phenomenon in which the offspring of two genetically different parents exhibit superior traits compared to their parents. The degree of heterosis is influenced by additive and non-additive gene effects (Sunny et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Because the tiny genetic base is a key bottleneck for breaking the yield plateau, it is vital to boost sunflower seed and oil yield by integrating additional genes from superior lines through recombination breeding. Plant breeders are very interested in genetic variety [ 7 – 9 ]. The more different the parents, the more likely a heterotic cross combination will result in F 1 with a wide range of diversity in segregating generations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%